Gender, resilience, and food systems - Bryan, Elizabeth; Ringler, Claudia; Meinzen-Dick, Ruth S. (Palgrave Macmillan, 2023)
Research on the gender dimensions of resilience highlights differences in the ways that men and women experience disturbances, their resilience capacities, and their preferred responses. This chapter incorporates a food systems lens into a gender and resilience framework to identify key entry points to strengthen women’s and men’s food security and nutrition in the face of multiple, reoccurring shocks and stressors. Drawing on systematic reviews and case studies from the literature, this chapter finds that exposure and sensitivity to disturbances depend largely on gendered roles in food systems, including along agricultural value chains, and the food environments in which men and women live. Increasing women’s resilience capacities—which tend to be lower than men’s—through investments in education, information and financial services, employment opportunities, and women’s agency, can improve food security and nutrition outcomes and increase their contribution to food system resilience. Considering gender differences in needs and preferences in policy and intervention design is, therefore, essential to ensure that investments reach, benefit, and empower women as agents of change for greater resilience.